Nanocrystalline Pb(Zr0.52Ti0.48)O3 Ferroelectric Ceramics: Mechanical and Electrical Properties. (2nd June 2010) - Ramana, M. Venkata; Reddy, M. Penchal; Reddy, N. Ramamanohar; Kumar, K. V. Siva; Murthy, V. R. K.; Murty, B. S.
Abstract : Nanocrystalline powders of the composition Pb ( Zr 0.52 Ti 0.48 ) O 3 were obtained by Mechanical alloying (high-energy ball milling). X-ray diffraction studies show that these compounds are completely into the perovskite phase. Detailed studies of electrical and mechanical properties of PZT as a function of temperature (and frequency) showed the high permittivity of 20653 at Curie transition temperature. Temperature variation of longitudinal modulus and internal friction of these ceramics at 104 kHz frequency were studied in the wide temperature range of 30 ∘ C–420 ∘ C. The internal friction measurements showed sharp stress induced relaxation peaks in the present composition corresponding to those temperatures where the minima were noticed in temperature variation of longitudinal modulus behavior. This dielectric and internal friction behaviour was explained in the light of polaron hopping mechanism and structural phase transitions in the present piezoelectric compositions.